Role of Certain Growth Regulators on the Vegetative Propagation of a Desert Species - Ipomoea Biloba forsk - Sharma, Shyam S.; Sen, David N. (Indian Forester, 1973)
In the present paper, the role of certain growth regulators (SADH, ethr's, GA, HA, IAA AND MH) have been studied with regards to the vegetative propagation of a desert species-Ipomoea biloba. It has emerged from present study that 2,4-D, ethrel and MH did not produce much favourable effect either on rooting or axillary bud formation. The best effect among the growth regulators investigated here was that of IAA and humic acid on rooting and that of GA on axillary bud formation and shoot growth.